Role of mHealth in overcoming the occurrence of post-stroke depression - Miranda J.J. (2018)
Depression associated with stroke affects roughly one-third of stroke survivors. Post-stroke depression (PSD) is thought to adversely influence functional outcome by limiting participation in rehabilitation, decreasing physical, social, and cognitive function, and affecting neuroplasticity thereby placing stroke survivors at high risk for future vascular events. PSD has also been associated with higher mortality rates after stroke. In Peru, a country where there is no national stroke program and mental health disorders are largely underdiagnosed and untreated, people with PSD are likely to be further challenged by dependency and impoverished conditions that will limit their use of ambulatory services, leading to inadequate clinical follow-up. In this scenario, mobile health (mHealth) technology offers a promising approach to extend access to high-quality and culturally tailored evidence-based psychological care to address PSD given that cell phone use, Internet connectivity, and digital health technology have met a rapid growth in the last years and thus contribute to the attainment of broader Sustainable Development Goals (SDGs).